2014
DOI: 10.1051/shsconf/20141201098
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity of Ficus Hispida as a Local Traditional Product in the Lembah Lenggong World Heritage Site

Abstract: Abstract. Lembah Lenggong is a place well known amongst locals as an archaeological site; the valley has been attested as a World Heritage Site. There is an overwhelming variety of plant species that are uniquely used in their cultural and traditional cuisines including Ficus hispida (Senia). Ficus hispida is a well-known species restricted to the native people in Lembah Lenggong. It is recognized as one of the plants used specifically in the traditional cuisine of the locals, especially amongst the old folks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
3
0
0
Order By: Relevance
“…Interestingly, no informant in our study, not even local healers, reported that the fruit is harmful. Similar findings on edible leaf shoots and fruits of F. hispida has been reported in Malaysia [53]. Although no toxicity information was reported in the current study, this species should be studied further to determine the efficacy and safety evaluation for consumption.…”
Section: Food Uses Of Fig Species Compared To Other Studiessupporting
confidence: 77%
“…Interestingly, no informant in our study, not even local healers, reported that the fruit is harmful. Similar findings on edible leaf shoots and fruits of F. hispida has been reported in Malaysia [53]. Although no toxicity information was reported in the current study, this species should be studied further to determine the efficacy and safety evaluation for consumption.…”
Section: Food Uses Of Fig Species Compared To Other Studiessupporting
confidence: 77%
“…Interestingly, no informant in our study, not even local healers, reported that the fruit is harmful. Similar ndings on edible leaf shoots and fruits of F. hispida has been reported in Malaysia [53]. Although no toxicity information was reported in the current study, this species should be studied further to determine the e cacy and safety evaluation for consumption.…”
Section: Food Uses Of G Species Compared To Other Studiessupporting
confidence: 71%
“…Interestingly, no informant in our study, not even local healers, reported that the fruit is harmful. Similar ndings on edible leaf shoots and fruits of F. hispida has been reported in Malaysia [45]. Although no toxicity information was reported in the current study, this species should be studied further to determine the e cacy and safety evaluation for consumption.…”
Section: Food Uses Of Fig Species Compared To Other Studiessupporting
confidence: 71%